Fructose 2,6-Bisphosphate in Cancer Cell Metabolism - Bartrons, Ramon; Simon-Molas, Helga; Rodríguez-García, Ana; Castaño, Esther; Navarro-Sabaté, Àurea; Manzano, Anna; Martinez-Outschoorn, Ubaldo E. (Frontiers in Oncology, 2018)
For a long time, pioneers in the field of cancer cell metabolism, such as Otto Warburg, have focused on the idea that tumor cells maintain high glycolytic rates even with adequate oxygen supply, in what is known as aerobic glycolysis or the Warburg effect. Recent studies have reported a more complex situation, where the tumor ecosystem plays a more critical role in cancer progression. Cancer cells display extraordinary plasticity in adapting to changes in their tumor microenvironment, developing strategies to survive and proliferate. The proliferation of cancer cells needs a high rate of energy and metabolic substrates for biosynthesis of biomolecules. These requirements are met by the metabolic reprogramming of cancer cells and others present in the tumor microenvironment, which is essential for tumor survival and spread. Metabolic reprogramming involves a complex interplay between oncogenes, tumor suppressors, growth factors and local factors in the tumor microenvironment. These factors can induce overexpression and increased activity of glycolytic isoenzymes and proteins in stromal and cancer cells which are different from those expressed in normal cells. The fructose-6-phosphate/fructose-1,6-bisphosphate cycle, catalyzed by 6-phosphofructo-1-kinase/fructose 1,6-bisphosphatase (PFK1/FBPase1) isoenzymes, plays a key role in controlling glycolytic rates. PFK1/FBpase1 activities are allosterically regulated by fructose-2,6-bisphosphate, the product of the enzymatic activity of the dual kinase/phosphatase family of enzymes: 6-phosphofructo-2-kinase/fructose 2,6-bisphosphatase (PFKFB1-4) and TP53-induced glycolysis and apoptosis regulator (TIGAR), which show increased expression in a significant number of tumor types. In this review, the functionof these isoenzymes in the regulation of metabolism, as well as the regulatory factors modulating their expression and activity in the tumor ecosystem are discussed. Targeting these isoenzymes, either directly or by inhibiting their activating factors, could be a promising approach for treating cancers.